Effect of nanoparticulate CaCO3 on the biological properties of calcium silicate cement - Quang Canh Vo; Gitae Son; Gyeung Mi Seon; Sun Woo Um; Sang Hoon Choi; Hyeong-Cheol Yang (Scientific Reports)
Abstract This study aimed to evaluate the effects of nanoparticulate CaCO3 (NPCC) on the biological properties of calcium silicate-based cements (CSCs), including their cytotoxicity, in vitro osteogenic activity, and interactions with rat femur tissue. The average size of NPCC was 90.3±26.0 nm. Cytotoxicity and osteogenic activity assays were performed using mouse bone marrow mesenchymal stem cells (BMSCs). BMSCs exposed to the eluents from CSC alone and CSC containing 2.5% NPCC (CSC-NPCC (2.5%)) for 24 h showed decreased cell viability at an eluent concentration of 75%. In contrast, CSC-NPCCs (5%, 10%, and 20%) did not affect cell viability. Regarding osteogenic activity, CSC-NPCCs (5%, 10%, 20%) enhanced the expression of osteogenic genes, including runt-related transcription factor 2 (RUNX2), alkaline phosphatase (ALP), type I collagen (COL-1), and osteocalcin (OCN). Additionally, mineralization in cell cultures was enhanced by CSC-NPCC, indicating that NPCC promoted the osteogenic activity of CSCs. In rat femurs, NPCC accelerates CSC resorption and stimulates bone regeneration at the implantation site. CSC alone occupied 22.2%±3.25% of the total femoral area at the implantation site, whereas CSC-NPCC (20%) occupied only 4%. These histological findings suggest that CSC-NPCC has potential as a biodegradable bone cement for use in bone defect areas that require regeneration.